INTEGRATION OF TECHNOLOGY IN THE IMPLEMENTATION OF TECHNICAL GUIDANCE FOR VILLAGE/SUB-DISTRICT COOPERATIVES IN MERAH PUTIH GORONTALO - Paputungan, Frezy; Khotimah, Husnul; Ibura, Irvan (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
Technology is an applied science that encompasses a set of tools, systems, methods, and skills used by humans to solve problems and make work easier. The word comes from the Greek 'techne' (art, craft, skill) and 'logos' (science). Some examples of technology vary from simple tools such as prehistoric axes to complex systems such as the internet, which enable humans to innovate and improve the quality of life. The method used in this study is library research, which collects and analyzes various related literature to explore the concept of technology, and the integration model in the implementation of KDKMP technical guidance in Gorontalo, as well as the role of the cooperative office and facilitators in its implementation. The findings indicate that the management and implementation of KKDMP Technical Guidance runs smoothly and with quality thanks to the use of technology. In addition, cooperative facilitators who pass the 2025 test from the Ministry of Cooperatives are expected to be able to implement practices in accordance with the implementation journal and applicable regulations effectively. The Red and White Cooperative is a government program to establish village/sub-district-based economic institutions that aim to improve the welfare and independence of the community through the principles of mutual cooperation and kinship. This cooperative functions as a joint forum for carrying out various local economic efforts, such as providing basic necessities, savings and loan services, and strengthening MSMEs, so as to encourage food security and shorten the supply chain. The Red and White Cooperative Program (Kopdes Merah Putih) is a national initiative to establish cooperatives in every village and sub-district to strengthen the local economy and improve community welfare through the principles of mutual cooperation.